AXIAL TENSILE STRENGTH ANALYSIS OF UNBONDED FLEXIBLE PIPE CONTAINING COMPOSITE TENSILE ARMORS - MA JinSheng; DU FaXi; LUO Dan (Jixie qiangdu)
As offshore oil industry moves into ultra-deep water,replacing the steel tensile armors of unbonded flexible pipe with composite is becoming a scheme that can effectively reduce weight and provide better mechanical properties.The anisotropic parameters of composite are obtained by meso-mechanical method,then a model of axisymmetric structure response for composite flexible pipe with composite armored layer is established,which is based on both thick-wall cylinder theory and the differential equation of curved beam,and also the algorithm of cyclic iterative is combined.Failure models of different type of flexible pipes are obtained,and iso-strength method is used for composite armored pipe.A case study shows that composite armors can effectively enhance the tensile strength of unbonded flexible pipe while effectively reduce the overall weight.Results state that volume fraction,elastic modulus and strength of fiber are the important parameters which affect the axial stiffness and tensile strength of unbonded flexible pipe.